Des controverses en éducation au paysage : quels enjeux éducatifs, finalités didactiques et modalités pédagogiques ? - Virginie Albe (Projets de Paysage)
In this article, we have attempted to more clearly define the different roles assigned to controversies when these are used in teaching landscape architecture and science in order to develop a sense of citizenship. To do so we conducted two literature reviews in geography and urban planning and in social sciences and educational sciences. By using the CNRS bibliographical portal two different corpuses were constituted. A main corpus intended for the study of landscape controversies, comprising 44 scientific articles published in French and English, and a secondary corpus for the study of socio-scientific controversies, comprising 36 articles published in French and English. We discussed the modalities for the integration within the curriculum of controversies according to the different roles assigned to them in terms of educational research, contexts, objectives and means.